2023
DOI: 10.58803/rbes.2023.2.1.01
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Probiotics to Combat Urinary Tract Infections: A Comprehensive Review

Ali Qasemi,
Milad Lagzian,
Fateh Rahimi
et al.

Abstract: Urinary tract infections (UTIs) are among the most common bacterial infections and can cause significant morbidity, particularly in women. Recurrent UTIs are a significant clinical problem, and current prophylactic measures, such as antibiotics, are associated with side effects and the risk of antimicrobial resistance. Probiotics, defined as live microorganisms that confer health benefits to the host, have emerged as a potential alternative to traditional treatments for recurrent UTIs. Probiotics can act by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The divergence in conclusions among studies may be attributed to the varying efficacy of probiotics, which heavily depends on the strain, dosage, and timing of administration. Currently, there is no consensus regarding the optimal dosing and duration of viable probiotic use for combating UTIs [ 40 ]. Notably, it may not be appropriate to directly compare the findings of our study with previous reports, as most of the existing literature focuses on viable probiotic supplementation for the prevention of recurrent UTIs, whereas our study primarily concentrates on the treatment of UTIs.…”
Section: Resultsmentioning
confidence: 99%
“…The divergence in conclusions among studies may be attributed to the varying efficacy of probiotics, which heavily depends on the strain, dosage, and timing of administration. Currently, there is no consensus regarding the optimal dosing and duration of viable probiotic use for combating UTIs [ 40 ]. Notably, it may not be appropriate to directly compare the findings of our study with previous reports, as most of the existing literature focuses on viable probiotic supplementation for the prevention of recurrent UTIs, whereas our study primarily concentrates on the treatment of UTIs.…”
Section: Resultsmentioning
confidence: 99%
“…Various types of soil, water, and sediment samples have been investigated to identify phenol-degrading microorganisms, which can be applied to reduce phenol pollu-tion in the environment. In most cases, the results obtained in this research indicated that the C. testosteroni strain F4 bacteria isolated from the soil of pistachio orchards in Kerman, Iran, can be used to biodegrade phenol [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%